Autonomic nervous system responses as performance indicators among volleyball players - Collet, C.; Roure, R.; Delhomme, G.; Dittmar, A.; Rada, H.; Vernet-Maur , E. (European Journal of Applied Physiology, 1999)
The aim of this study was to verify that autonomic responses reflect the quality of central motor programming leading to successful or failed performance when subjects are required to perform a complex motor skill.